Laboratory Maintenance and Growth of Talaromyces marneffei. Issue 1 (10th February 2020) - Andrianopoulos, Alex
Abstract: Talaromyces marneffei is an important opportunistic human pathogen endemic to Southeast Asia. It is one of a number of pathogenic fungi that exhibits thermally controlled dimorphism. At 25°C, T. marneffei grows in a multicellular, filamentous hyphal form that can differentiate to produce dormant spores called conidia. These conidia are the likely infectious agent. At 37°C, T. marneffei grows as a uninucleate yeast that divides by fission. The yeast cells are the pathogenic form of this fungus. The protocols described here explain how to grow T. marneffei in the two vegetative growth forms in vitro, grow yeast cells inside mammalian macrophages, produce conidial stocks, and store strains both short and long term. © 2020 by John Wiley & Sons, Inc. Basic Protocol 1 : Growth of the vegetative hyphal form on solid medium Alternate Protocol 1 : Growth of the vegetative hyphal form in liquid suspension Basic Protocol 2 : Growth of the vegetative yeast form on solid medium Alternate Protocol 2 : Growth of the vegetative yeast form in liquid suspension Basic Protocol 3 : Growth for production of dormant conidia Support Protocol : Preparation of Miracloth filter tubes Basic Protocol 4 : Growth of Talaromyces marneffei in mammalian macrophages Basic Protocol 5 : Storage of Talaromyces marneffei strains Alternate Protocol 3 : Lyophilization of Talaromyces marneffei strains